Religious Moderation Education According To Islamic Scholars In Gowa Regency South Sulawesi - Muhammad Rais (EDUCANDUM, 2021)
This research is oriented to describe the perspective of public leaders on the educational discourse of religious moderation. which is currently being pursued by the government through the Ministry of Religion Affairs, so that it becomes the mainstream in religion. The principles of religious moderation include: nationality, tolerance, nonviolence, and local cultural accommodation. projected to be internalized, disseminated in all fields, including in educational institutions. Focuses on utilizing qualitative methods with specific data collection and analysis instruments, This study found that the informants, consisting of educators and religious figures, deeply understood religious moderation based on the al-Qur’an and hadith which emphasized Islam as a moderate religion. The principle of moderation (wasathiyyah) in Islam is in fact equivalent to the principle or value of religious moderation programmed by the current government. Then, if the idea of religious moderation is to be implemented in the realm of education, then some components should be prepared carefully, so that they do not overlap, and even duplicate with other programs. For example, several implementation models chosen, of course, with their respective advantages and disadvantages, include: autonomous, integrative, and enrichment models. In addition, what is also very urgent to formulate is the right curriculum, tools and learning designs, and competencies of educators, including an assessment tool which of course is more oriented towards attitudes and behavior. No longer trapped in the pathology of learning that has been ongoing, more focused on fulfilling the cognitive domain.